Three hitherto undescribed species of Corynespora Gussow from North-eastern U.P. - K. SHUKLA; D.K. AGRAWAL, RAGHVENDRA SINGH, SHAMBHU KUMAR (Indian Phytopathology, 2007)
This communication deals with the descriptions, latin diagnoses and illustrations of three hitherto undescribed species of hyphomycetous fungus genus Corynespora Gussow viz., C. hyalophora sp. nov., C. hydrophila sp. novoand C. quisqualidis sp. novocollected on the living leaves of Glycosmis pentaphylfa (Rutaceae), Nymphaea sp. (Nymphaeaceae) and Quisqualis indica (Combretaceae) respectively, from North eastern Uttar Pradesh. Morphotaxonomic determination being done on comparison with allied taxa in question and current literature.